Breaking the Mold: Traits That Shape Succession Success in Small Family Businesses - Ahmad, Zeshan; Iftikhar, Hina; Iram, Tahira; Mohd Mustamil, Norizah (European Journal of Family Business, 2025)
This study examined how entrepreneurial personality traits influence perceived succession success, considering the daughter successor’s willingness to lead as a mediating factor. This study targeted the daughter successors designated as chairwomen or managing directors in the small-family business (S-FB) retail sector. A purposive sampling technique was used, and the sample size was 236. Using trait activation theory, we induced two filter questions to determine the unbiased relationship of exogenous, endogenous, and mediating variables. The daughter successor’s innovativeness traits have a positive significance, while internal locus of control and autonomy traits have non-significant associations with perceived succession success. Daughters with traits of innovativeness and a strong internal locus of control show a positive significance, whereas autonomy does not significantly relate to their willingness to take on leadership roles. Furthermore, the daughter successor’s readiness to lead partially mediates the relationship between innovativeness and perceived succession success, fully mediates the connection between an internal locus of control and succession success, and shows no mediation between autonomy traits and perceived succession success in S-FB. The successor’s unwillingness to lead results in succession failure and the closing down of family businesses. Through the support of trait activation theory, this study revealed that the allocation of job responsibilities and the provision of values, traditions, and cultural cues congruent with the successor’s personality traits not only increase her interest in leading but also enhance the likelihood of succession success for her family business.